Biological characterization of implant surfaces - in vitro study - Priscilla Barbosa Ferreira Soares; Camilla Christian Gomes Moura; Huberth Alexandre da Rocha Júnior; Paula Dechichi; Darceny Zanetta-Barbosa
Abstract Objective Evaluate the biological performance of titanium alloys grade IV under different surface treatments: sandblasting and double etching (Experimental surface 1; Exp1, NEODENT); surface with wettability increase (Experimental surface 2; Exp2, NEODENT) on response of preliminary differentiation and cell maturation. Material and method Immortalized osteoblast cells were plated on Exp1 and Exp2 titanium discs. The polystyrene plate surface without disc was used as control group (C). Cell viability was assessed by measuring mitochondrial activity (MTT) at 4 and 24 h (n = 5), cell attachment was performed using trypan blue exclusion within 4 hours (n = 5), serum total protein and alkaline phosphatase normalization was performed at 4, 7 and 14 days (n = 5). Data were analyzed using one-way ANOVA and Tukey test. Result The values of cell viability were: 4h: C- 0.32±0.01A; Exp1- 0.34±0.08A; Exp2- 0.29±0.03A. 24h: C- 0.43±0.02A; Exp1- 0.39±0.01A; Exp2- 0.37±0.03A. The cell adhesion counting was: C- 85±10A; Exp1- 35±5B; Exp2- 20±2B. The amounts of serum total protein were 4d: C- 40±2B; Exp1- 120±10A; Exp2- 130±20A. 7d: C- 38±2B; Exp1- 75±4A; Exp2- 70±6A. 14 d: C- 100±3A; Exp1- 130±5A; Exp2- 137±9A. The values of alkaline phosphatase normalization were: 4d: C- 2.0±0.1C; Exp1- 5.1±0.8B; Exp2- 9.8±2.0A. 7d: C- 1.0±0.01C; Exp1- 5.3±0.5A; Exp2- 3.0±0.3B. 14 d: C- 4.1±0.3A; Exp1- 4.4±0.8A; Exp2- 2.2±0.2B. Different letters related to statistical differences. Conclusion The surfaces tested exhibit different behavior at dosage of alkaline phosphatase normalization showing that the Exp2 is more associated with induction of cell differentiation process and that Exp1 is more related to the mineralization process.